Tuberculosis reactivation related with ruxolitinib in a patient with primary myelofibrosis - Mehmet S Pepeler; Zübeyde N Özkurt; Özlem T Güzel; Nalan Akyürek (Journal of Infection in Developing Countries)
Primary myelofibrosis (PMF) is a clonal stem cell disease, characterized by bone marrow fibrosis. Ruxolitinib is a selective inhibitor of JAK-1 and JAK-2 used to treat PMF. Its mechanism of action is based on the reduction of signal transduction and cytokine levels; including IL-6 and tumor necrosis factor alpha. Increased infection risk related to Ruxolutinib is rarely reported. Here we describe a case of tuberculosis infection ractivation in a female patient treated with Ruxolitinib. During the treatment, she complained of night sweats, weight loss and enlarged mass in the neck. Excisional mass biopsy revealed a necrotizing granulomatous lymphadenitis. QuantiFERON-TB and PPD tests were not able to diagnose the tuberculosis infection. Therapy with Ruxolitinib was interrupted due to possible immunsuppressive effects and the patient was treated with the standard antituberculosis regimen. After six months, the patient’s symptoms had resolved and there was no lymphoadenopathy. In conclusion, it is important to assess the risk of tuberculosis activation before Ruxolitinib treatment. In addition, the diagnosis of tuberculosis using QuantiFERON-TB and PPD may be misleading in patients treated with Ruxolutinib.